Development and piloting of a prevention assessment and response tool for healthcare-associated Staphylococcus aureus bloodstream infection (the SAB-PART Study) using a Delphi method. (September 2021) - Karanfilovska, D.; Cheng, A.C.; Spelman, D.; Worth, L.J.
Summary: Background: Healthcare-associated Staphylococcus aureus bloodstream infection (HA-SAB) causes preventable harm in hospitalized patients. Currently, there is no standardized method available to review HA-SAB events in order to identify and target preventable risks requiring action at an organizational level. Aim: To develop a tool to classify SAB events, and the necessary response actions, according to the degree of preventability. Methods: Following a literature review, a tool was developed. Consensus feedback and development of the tool was sought from experts ( N = 11) in healthcare-associated infection surveillance using a Delphi technique. The completed tool was retrospectively applied to HA-SAB events ( N = 43) that occurred at a large healthcare organization. Findings: Survey completion rates were high (91–100%). Clinicians' poor adherence to infection prevention practices and lack of engagement with feedback processes was established as the key modifiable element. A second key theme was the need for structured and detailed response actions. This feedback was incorporated into the tool and refined until consensus on all elements was achieved. Pilot application of the tool found that 56% of HA-SAB events were highly or possibly preventable; modifiable factors for HA-SAB prevention were not present in the remainder of cases. Conclusion: A prevention assessment and response tool was successfully developed via a consensus method to assist organizations in investigating and responding to individual cases of HA-SAB and identify future priority areas for SAB reduction strategies. Wider use of the tool with routine surveillance activities is required to evaluate impact upon infection prevention programmes and patient outcomes.